التنبؤ بمبيعات البنك المركزي من العملة الأجنبية باستخدام (أنموذج دالة التحويل العشوائي) (المجلة العراقية للعلوم الاقتصادية, 2018)
The Transfer Function – Noise Models have an important role in Multivariate Time Series Analysis , and it consider as one of the Subjects that have an urgent Application in Economic ,Industrial fields , …, ect . The Application was on monthly data of time series , namely , Demand gap of foreign currency , and the sales of foreign currency . The studied Model , the Transfer Function – Noise with single inputs – single output ( SISO ) is compared with other suggested Model , namely , ARMA Model , and it is found that the studied Model is the best depends on the measurements MSE , NAIC , NBIC .